The Physiopathology of T- Cell Acute Lymphoblastic Leukemia: Focus on Molecular Aspects - Fattizzo, Bruno; Rosa, Jessica; Giannotta, Juri Alessandro; Baldini, Luca; Fracchiolla, Nicola Stefano (Frontiers in Oncology, 2020)
T-cell acute lymphoblastic leukemia/ lymphoma is an aggressive haematological neoplasm whose classification is still based on immunephenotypic findings. Frontline treatment encompass high intensity combination chemotherapy with good overall survival; however, relapsing/refractory patients have very limited options. In the last years, the understanding of molecular physiopathology of this disease, lead to the identification of a subset of patients with peculiar genetic profile, namely “early T-cell precursors” lymphoblastic leukemia, characterized by dismal outcome and indication to frontline allogeneic bone marrow transplant. In general, the most common mutations occur in the NOTCH1/FBXW7 pathway (60% of adult patients), with a positive prognostic impact. Other pathogenic steps encompass transcriptional deregulation of oncogenes/oncosuppressors, cell cycle deregulation, kinase signaling (including IL7R-JAK-STAT pathway, PI3K/AKT/mTOR pathway, RAS/MAPK signaling pathway, ABL1 signaling pathway), epigenetic deregulation, ribosomal disfunction, and altered expression of oncogenic miRNAs or long non coding RNA. The insight in the genomic landscape of the disease paves the way to the use of novel targeted drugs that might improve the outcome, particularly in relapse/refractory patients. In this review, we analyse available literature on T-ALL pathogenesis, focusing on molecular aspects of clinical, prognostic, and therapeutic significance.